Smartphone based music intervention in the treatment of episodic migraine headaches - A pilot trial - Guilhem Parlongue; Emmanuelle Vuillaume Cerdan; Julian Koenig; DeWayne P. Williams (Elsevier, 2021)
Objectives: Migraine headaches are a prevalent and burdening disorder for the public worldwide. Both traditional preventive drugs and behavioral-based interventions have been used as treatment in the prevention of migraine attacks. However, benefits of alternative interventions in patients with primary headache disorders have not yet been fully explored.The present investigation sought to examine the impact of a patient controlled music intervention (MUSIC CARE) on episodic migraine headache. Design: A sample of 20 episodic migraine patients (17 females, mean age of 42 years) was included in the pilot trial. Patients completed a pre-treatment assessment on headache severity, associated psychopathological distress (anxiety and depression) and functional impairment, and provided reports on their medication intake. During the 3-months intervention period, patients required 1-2 music sessions (based on the "U" sequence) per day with a minimum of 15 per month. Results: Following the intervention, patients reported a significant reduction in the frequency of migraine attacks (MDiff = −2.8, p = .01). Ten patients reported a 50% reduction in the frequency of migraine attacks. Additionally, there was a significant reduction in medication intake (MDiff = −2.85, p = .02), the duration of migraine attacks (MDiff = −5.45, p = .002), anxiety (MDiff = −1.65 (2.88), p = .02) and depression (MDiff = −2.45 (3.5), p = .002). Conclusion: These data provide evidence that music intervention may significantly prevent migraine attacks. Moreover, this method is easily accessible and administered. Future well-controlled clinical trials are necessary to further explore the efficiency of the intervention.